APPLICATION OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING CHEMICAL EQUILIBRIUM IN ANALYTICAL CHEMISTRY COURSES AT UNIVERSITIES - Turgunboev Shavkatjon Shuhratjon ugli (Bright Mind Publishing, 2025)
The teaching of chemical equilibrium in analytical chemistry remains one of the most conceptually demanding topics for undergraduate students. Over the last fifteen years, educators have increasingly integrated modern pedagogical technologies to enhance students’ conceptual understanding, engagement, and problem-solving skills. This review synthesizes peer-reviewed studies published between 2010 and 2025 that investigate the application of digital, interactive, and student-centered teaching strategies in university-level chemistry education. The analysis identifies three dominant pedagogical trends: (1) the use of digital and interactive technologies such as PhET simulations, virtual and augmented reality (VR/AR), and digital laboratories; (2) the implementation of game-based learning and peer-led team learning (PLTL) to improve motivation and collaborative reasoning; and (3) integrative hybrid approaches that combine technological, pedagogical, and content knowledge (TPACK framework). The reviewed studies demonstrate that modern technologies significantly improve short-term engagement and conceptual understanding but vary in their long-term impact. The paper concludes with recommendations for higher education institutions to design evidence-based, integrative pedagogical models for teaching chemical equilibrium in analytical chemistry courses.
Keywords: Analytical chemistry education; chemical equilibrium; pedagogical technologies; interactive simulations; game-based learning; peer-led team learning; digital chemistry teaching.